2013
DOI: 10.1021/jo401083m
|View full text |Cite
|
Sign up to set email alerts
|

Gold-Catalyzed Domino Aminocyclization/1,3-Sulfonyl Migration of N-Substituted N-Sulfonyl-aminobut-3-yn-2-ols to 1-Substituted 3-Sulfonyl-1H-pyrroles

Abstract: A method to prepare 1-substituted 3-sulfonyl-1H-pyrroles efficiently that relies on the gold(I)-catalyzed cycloisomerization of N-substituted N-sulfonyl-aminobut-3-yn-2-ols is described. The method was shown to be applicable to a broad range of 1,7-enyne alcohols containing electron-withdrawing, electron-donating, and sterically demanding substrate combinations. The mechanism is suggested to involve activation of the propargylic alcohol by the Au(I) catalyst, which causes the intramolecular nucleophilic additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(22 citation statements)
references
References 57 publications
1
21
0
Order By: Relevance
“…Subsequently, Chan’s group presented a gold-catalyzed domino aminocyclization/1,3-sulfonyl migration of N -substituted N -sulfonyl-aminobut-3-yn-2-ols 111 to synthesize highly functional pyrroles 112 (Scheme 35) [49]. A screening of gold catalysts disclosed that the NHC ( N -heterocyclic carbene)-gold(I) complex 113 was found to be the most effective catalyst for this intramolecular aminosulfonylation of alkynes.…”
Section: Transition-metal-catalyzed Addition Of Sulfonamide Bonds mentioning
confidence: 99%
“…Subsequently, Chan’s group presented a gold-catalyzed domino aminocyclization/1,3-sulfonyl migration of N -substituted N -sulfonyl-aminobut-3-yn-2-ols 111 to synthesize highly functional pyrroles 112 (Scheme 35) [49]. A screening of gold catalysts disclosed that the NHC ( N -heterocyclic carbene)-gold(I) complex 113 was found to be the most effective catalyst for this intramolecular aminosulfonylation of alkynes.…”
Section: Transition-metal-catalyzed Addition Of Sulfonamide Bonds mentioning
confidence: 99%
“…Initially, the α-position of sulfonyl group would undergo lithiation upon treatment with LDA to deliver A and then a 4-exo-dig cyclization would occur to generate four-membered β-sultam intermediate B 63 , 64 , 67 , 68 . Subsequently, B presumably undergoes a 1,3-sulfonyl migration to form lithium thiete sulfone intermediate C 69 , 70 , which could be protonated by MeOH to deliver product 2 . When MeOH was replaced by other electrophilic reagents, intermediate C could be functionalized directly to obtain N -substituted thiete sulfone products.…”
Section: Resultsmentioning
confidence: 99%
“…A cross‐over experiment demonstrated that the migration proceeds intramolecularly. This was further witnessed by the lack of reaction of a 3‐unsubstituted pyrrole (no SO 2 R 5 ) with TsCl in the presence of the same catalyst 39…”
Section: N‐nucleophilesmentioning
confidence: 99%